2021
DOI: 10.1080/00036846.2020.1870651
|View full text |Cite
|
Sign up to set email alerts
|

Global financial interconnectedness: a non-linear assessment of the uncertainty channel

Abstract: The role of uncertainty in the global economy is now widely recognized by policy-makers but its specific effects on the international financial system are less understood. In this paper we assess the impact of uncertainty fluctuations on the interconnectedness within the international system of equity prices. In this respect, we extend the measure of connectedness put forward by Diebold and Yilmaz ( 2009) by allowing for non-linear effects through the estimation of a non-linear Threshold VAR model whose regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Youssef et al (2020) utilized the TVP-VAR to document that the European stock markets transmit more shocks than they receive from all other stock markets during the COVID-19 pandemic. In line with the work of Diebold and Yilmaz (2015), Candelon et al (2018) documented that the major net transmitters of shocks are the United States and the United Kingdom, while other countries in their connectedness framework are net receivers of financial shocks. Also, Shahzad et al (2018) Another strand of the literature examines how the GFC altered the connectedness, analysing the periods before and after this crisis.…”
Section: Literature Reviewmentioning
confidence: 62%
“…Youssef et al (2020) utilized the TVP-VAR to document that the European stock markets transmit more shocks than they receive from all other stock markets during the COVID-19 pandemic. In line with the work of Diebold and Yilmaz (2015), Candelon et al (2018) documented that the major net transmitters of shocks are the United States and the United Kingdom, while other countries in their connectedness framework are net receivers of financial shocks. Also, Shahzad et al (2018) Another strand of the literature examines how the GFC altered the connectedness, analysing the periods before and after this crisis.…”
Section: Literature Reviewmentioning
confidence: 62%
“…Some studies have used other measures of interconnectedness as a link in the bank network; these include credit default swap contracts (Ballester, Casu, & González-Urteaga, 2016;Gandy & Veraart, 2019;Kanno, 2018;Peltonen, Scheicher, & Vuillemey, 2014), and cross-ownership of equity shares (Cao, Gregory-Smith, & Montagnoli, 2018;Dastkhan & Gharneh, 2016, 2018Elliott et al, 2014;Elsinger, 2009). However, bank network, as defined in our study, is based on economic connections identified from stock market data (i.e., correlation network of stock return dynamics), as in Diebold and Yilmaz (2014), Brunetti et al (2015), and Candelon, Ferrara, and Joëts (2018). This view is generally accepted in the literature, as high correlations in the bank equity sector are the main source of systemic risk in the bank network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To serve as control variables, we collected the following: the European EPU index was collected from [61], the shadow rate for the ECB from [62], and the German VIX from [63]. The EPU index was previously found to be a significant factor in affecting the dynamics of stock markets in Europe and CESEE countries, as seen in [12,[64][65][66][67][68]. The effects of monetary policy on stock market dynamics have been significant for a long time now (see [69][70][71][72]).…”
Section: Data Descriptionmentioning
confidence: 99%